Early arteriovenous fistula after radiofrequency ablation of long saphenous vein. (December 2013) - Ahmad, A; Sajjanshetty, M; Mandal, A; Hamilton, H
A 75-year-old woman developed an arteriovenous fistula (AVF) between the common femoral artery and common femoral vein following radiofrequency ablation (RFA) of left long saphenous vein. Failed coil embolization of the AVF was followed by successful surgical ligation. Awareness of the aetiology of this uncommon complication of RFA and its treatment options is important with the increasing use of RFA for varicose vein treatment.